Semantic types of directive complexes and relations between their components (based on material taken from the Russian literary dialogue) - Zadvornaya, Elena G.; Vitchenko, Ludmila V. (Journal of the Belarusian State University. Philology, 2024)
Two-component directive complexes used by the speakers in the Russian dialogical communication are considered. It is shown that depending on a semantic type of a verb these complexes can be divided into homogeneous and heterogeneous complexes. Four types of relations between components of directive complexes are described: 1) simultaneity relations; 2) consistency relations; 3) specification relations; 4) synonymy relations. It has been established that the type of relations between the components as well as the order of their interposition depends on a semantic type of a directive speech act.
Keywords: directive speech act; directive complex; homogeneous complex; heterogeneous complex; semantic varieties; syntactical relations